Hedgehog pathway proteins SMO and GLI expression as prognostic markers in head and neck squamous cell carcinoma. Issue 1 (28th May 2019) - Richtig, Georg; Aigelsreiter, Alena M; Asslaber, Martin; Weiland, Thomas; Pichler, Martin; Eberhard, Katharina; Sygulla, Stephan; Schauer, Silvia; Hoefler, Gerald; Aigelsreiter, Ariane
Abstract : Aims: Because the hedgehog signalling pathway plays a major role in many types of cancer and can nowadays be targeted by specific compounds, we aimed to investigate the role of this pathway in squamous cell carcinoma of the head and neck. Methods and results: Ninety‐eight treatment‐naive head and neck cancer specimens were immunohistologically stained for SMO, GLI‐1, p53 and p16 expression and correlated with clinicopathological factors. Immunoreactivity for SMO and GLI‐1 was found in 20 (20.4%) and 52 (53.1%) cases of tumours, respectively. SMO expression correlated with GLI‐1 expression (ρ = 0.258, P = 0.010) in univariate and multivariate analysis ( P = 0.007, t = 2.81). In univariate analysis, high SMO expression was associated with shorter overall survival (HR = 0.56; 95% CI = 0.32–0.98; P = 0.044) and disease‐free survival (HR = 0.53; 95% CI = 0.30–0.95; P = 0.034). In multivariate cox regression analysis SMO expression showed a trend towards an independent predictor for shorter overall survival (HR = 0.57; 95% CI = 0.30–1.05; P = 0.072) and disease‐free survival (HR = 0.53; 95% CI = 0.28–1.02; P = 0.056). In head and neck cancer patients with low tumour p16 expression, SMO expression was an independent factor for overall survival (HR = 0.49; 95% CI = 0.24–0.98; P = 0.043) and disease‐free survival (HR = 0.45; 95% CI = 0.22‐0.96; P = 0.037). Conclusion: Although it needs to be confirmed in larger cohorts, our results suggest that targeting SMO might be a potentially therapeutic option in patients with head and neck cancer. In line, molecular pathological analyses including mutation analysis in the hedgehog pathway might point to additional therapeutic leads.